Biped Gait Analysis based on Forward Kinematics Modeling using Quaternions Algebra - González Islas, Juan Carlos; Domínguez-Ramírez , Omar Arturo; López Ortega, Omar (Revista Mexicana de Ingenieria Biomedica, 2020)
Gait is the main locomotion way for human beings as an autonomous decision. Due to the increase in people with walking disabilities, the precision in gait analysis for purposes in clinical diagnosis, sports medicine or biomechanical research for the design of assistive technologies is of special relevance. The literature reports notable contributions in technological developments with diverse applications; and in some cases, algorithms for characterization and gait analysis; however, more studies related to gait kinematics are necessary, such as the solution proposed in this work. In this paper, we focus on studying the forward kinematics of the lower limbs in human gait, using in a novel way quaternions algebra as mathematical tool and comparative analysis with classical methods is established. Gait analysis unlike other works is carried out by evaluating the rotational and tilting movements of the pelvis, flexion-extension of the hip and knee; as well as dorsiflexion and plantarflexion of the ankle. Finally, an assessment of normal, mild crouch and severe crouch gaits in the three anatomical planes is performed; and a metric based on the Euclidean norm in the cartesian space is used to evaluate these gaits.